Ni-based alloy with excellent high-temperature oxidation resistance

By reducing or not adding Cr to the Ni-based alloy and adding Al, Si, Mn, V, B, Zr and Mo, the problem of Cr scale mixing in the positive electrode material manufacturing process of lithium battery is solved, and the Ni-based alloy is realized Excellent high temperature oxidation resistance and thermal processability.

CN119421966APending Publication Date: 2025-02-11PROTERIAL LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380049469.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-03-03
Filing Date
2023-07-13
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

In the manufacturing process of the positive electrode substance of the lithium battery, if the oxide scale containing Cr is mixed in, the lithium battery life will be shortened and its high temperature oxidation resistance will be improved.

Method used

By reducing or not adding Cr, Ni-based alloys containing Al, Si, Mn, V, B, Zr and Mo are used to maintain excellent high temperature oxidation resistance.

Benefits of technology

Even if the Cr content is reduced or Cr is not added, the Ni-based alloy can maintain excellent high-temperature oxidation resistance and maintain good thermal processing during the thermal processing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119421966A_ABST
    Figure CN119421966A_ABST
Patent Text Reader

Abstract

Provided is a Ni-based alloy having excellent resistance to high-temperature oxidation even when the Cr content is reduced. The Ni-based alloy comprises, in mass%, 2.0 to 5.0% of Al, 0.1 to 2.5% of Si, 0.1 to 1.5% of Mn, 0.4 to 3.0% of V, 0.001 to 0.05% of B, and 0.001 to 0.1% of Zr, with the balance being Ni and impurities. The Ni-based alloy further contains 2.0% or less of Mo in the component composition. These Ni-based alloys also have excellent hot workability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to Ni-based alloys. Background Art

[0002] Generally, parts such as trays used in oxidation furnaces and roasting furnaces use Ni-based alloys with excellent high-temperature oxidation resistance to prevent oxide scale generated by the parts from being mixed into the product. In addition, as such Ni-based alloys, for example, the following Ni-based alloys are proposed, which contain, by mass%, Al: 2.0-5.0%, Si: 0.1-2.5%, Cr: 0.8-4.0%, Mn: 0.1-1.5%, B: 0.001-0.01%, Zr: 0.001-0.1%, and the balance is composed of Ni and inevitable impurities (Patent Document 1). In addition, as such Ni-based alloys, for example, the following Ni-based alloys are proposed, which contain, by mass%, Al: 2.0-5.0%, Si: 0.1-2.5%, Mn: 0.1-1.5%, B: 0.001-0.01%, Zr: 0.001-0.1%, and the balance is composed of Ni and inevitable impurities (Patent Document 2).

[0003] The Ni-based alloys of Patent Documents 1 and 2 have excellent high temperature oxidation resistance and are therefore suitable as alloys for components such as baking trays for chip capacitors and baking trays for positive electrode materials of lithium batteries. In addition, the Ni-based alloy of Patent Document 1 is also suitable as an alloy for components of CVD devices, PVD devices, LCD devices, semiconductor manufacturing devices, and the like.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2014-080675

[0007] Patent Document 2: Japanese Patent Application Publication No. 2015-045035 Summary of the invention

[0008] Problem that the invention aims to solve

[0009] The excellent high temperature oxidation resistance of the Ni-based alloy of Patent Document 1 is also ensured by the effect of its Cr content. On the other hand, when the alloy of Patent Document 1 is used in a manufacturing device for a positive electrode material of a lithium battery, if an oxide scale containing Cr is mixed into the positive electrode material, its characteristics will deteriorate, and therefore, it can be considered that the life of the lithium battery will be shortened. Therefore, it is preferred that the Cr content can be reduced. Also, in this regard, the Ni-based alloy of Patent Document 2 is effective, but there is room for improvement in high temperature oxidation resistance.

[0010] Therefore, if the high temperature oxidation resistance of Patent Document 1 can be maintained even if the Cr content in the Ni-based alloy is reduced or even if no Cr is added, such a Ni-based alloy is advantageous in the above-mentioned respect.

[0011] An object of the present invention is to provide a Ni-based alloy capable of maintaining excellent high temperature oxidation resistance even when the Cr content is reduced (even when Cr is not added).

[0012] Solutions for solving problems

[0013] That is, the present invention is a Ni-based alloy, which is composed of the following components: Al: 2.0-5.0%, Si: 0.1-2.5%, Mn: 0.1-1.5%, V: 0.4-3.0%, B: 0.001-0.05%, Zr: 0.001-0.1%, and the balance is Ni and impurities. Preferably, V: 1.0-3.0%. In addition, the Ni-based alloy further contains Mo: 2.0% or less in the above components.

[0014] Effects of the Invention

[0015] According to the present invention, even if the Cr content is reduced (even if Cr is not added), the excellent high temperature oxidation resistance of the Ni-based alloy can be maintained. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is a diagram showing the outline of the repeated oxidation test performed in Examples.

[0017] Figure 2 This is a graph showing the results of repeated oxidation tests performed in Examples.

[0018] Figure 3 This is a graph showing the results of repeated oxidation tests performed in Examples.

[0019] Figure 4 This is a graph showing the results of repeated oxidation tests performed in Examples.

[0020] Figure 5 This is a graph showing the results of repeated oxidation tests performed in Examples.

[0021] Figure 6 It is a figure which shows the result of the tensile test performed in Example.

[0022] Figure 7 It is a figure which shows the result of the tensile test performed in Example. DETAILED DESCRIPTION

[0023] The present invention is characterized in that a Ni-based alloy is found that can maintain the high temperature oxidation resistance of Patent Document 1 even when the Cr content is reduced or no Cr is added. The reasons for limiting the numerical values ​​of the respective component elements in the composition of the Ni-based alloy of the present invention are described in detail below.

[0024] Al:

[0025] Al is an element that forms an aluminum oxide film on the surface of Ni-based alloys, improves high-temperature oxidation resistance, and reduces scale formation. However, when Al is excessive, γ' phase (Ni3Al intermetallic compound) precipitates in the matrix of Ni-based alloys, thereby reducing hot workability and making processing difficult.

[0026] Therefore, the Al content is 2.0 to 5.0 mass % (hereinafter referred to as "%), preferably 2.5% or more, more preferably 3.0% or more, further preferably 3.5% or more, and preferably 4.7% or less, more preferably 4.5% or less, further preferably 4.2% or less.

[0027] Si:

[0028] Si is an element that improves high temperature oxidation resistance. However, when it is too much, cracks are easily generated during hot working. Therefore, the Si content is 0.1 to 2.5%. It is preferably 0.3% or more, more preferably 0.6% or more, and further preferably 0.8% or more. In addition, it is preferably 2.2% or less, more preferably 1.9% or less, and further preferably 1.7% or less.

[0029] Mn:

[0030] Mn is an element that improves high temperature strength. However, when it is too much, the high temperature oxidation resistance decreases. Therefore, the Mn content is 0.1 to 1.5%. It is preferably 0.2% or more, more preferably 0.3% or more, and further preferably 0.4% or more. In addition, it is preferably 1.2% or less, more preferably 0.9% or less, and further preferably 0.6% or less.

[0031] V:

[0032] V is an element that improves high temperature oxidation resistance and is therefore a useful element to replace Cr. However, when it is too much, the amount of precipitation of the γ' phase (Ni3V intermetallic compound) increases and the hot workability decreases. Therefore, the V content is 0.4-3.0%. It is preferably 0.7% or more, more preferably 0.9% or more, and further preferably 1.0% or more. In addition, it is preferably 1.1% or more, more preferably 1.2% or more, and further preferably 1.3% or more. In addition, it is preferably 2.7% or less, more preferably 2.4% or less, and further preferably 2.1% or less. In addition, it is preferably 1.8% or less, more preferably 1.6% or less, and further preferably 1.4% or less.

[0033] B and Zr:

[0034] B and Zr have the effect of improving the hot forgeability of Ni-based alloys by co-existence. This is presumably because the co-inclusion of B and Zr strengthens the grain boundaries of the Ni-based alloy, thereby suppressing the occurrence of grain boundary fracture during hot forging.

[0035] Moreover, when B is too little, the desired improvement effect brought about by the above-mentioned effect cannot be obtained, and when it is too much, hot forgeability will be reduced. Therefore, the content of B is 0.001-0.05%. It is preferably 0.003% or more, more preferably 0.005% or more, and further preferably 0.007% or more. In addition, it is preferably 0.04% or less, more preferably 0.03% or less, further preferably 0.02% or less, and further preferably 0.01% or less.

[0036] In addition, when Zr is too little, the desired improvement effect brought by the above-mentioned effect cannot be obtained, and when it is too much, hot forgeability will be reduced. Therefore, the content of Zr is 0.001-0.1%. It is preferably 0.005% or more, more preferably 0.007% or more, further preferably 0.01% or more, and further preferably 0.03% or more. In addition, it is preferably 0.08% or less, more preferably 0.07% or less, further preferably 0.06% or less, and further preferably 0.04% or less.

[0037] Mo:

[0038] Mo helps to improve high temperature oxidation resistance and high temperature strength, so it is an element that can be contained as needed. In addition, since it can further improve high temperature oxidation resistance by adding a small amount, it is a useful element to replace Cr. However, if it is too much, the hot workability decreases due to the increase in high temperature strength. Therefore, even if Mo is contained, its content is less than 2.0%. It is preferably less than 1.6%, more preferably less than 1.2%, further preferably less than 0.8%, and further preferably less than 0.6%. In addition, when Mo is contained, it is preferably more than 0.1%, more preferably more than 0.2%, and further preferably more than 0.3%.

[0039] The Ni-based alloy of the present invention may contain the above-mentioned element species, with the balance being Ni and impurities. In this case, a certain content of Cr is allowed, for example, it may be set to 0 to 0.5%, preferably 0.3% or less, and more preferably 0.1% or less.

[0040] The Ni-based alloy of the present invention is not only excellent in high temperature oxidation resistance, but also excellent in hot workability, therefore, various hot workings such as forging and rolling can be performed on ingots to provide them in the shape of plates, wires, and pipes. In addition, as a fixture or component formed by these materials, for example, it can be used as a baking tray of a sheet capacitor, a baking tray of a lithium battery positive electrode material, a CVD device component, a PVD device component, an LCD device component, and a semiconductor manufacturing device component. Or, of course, it can be used for various purposes such as oxidation furnace components, baking furnace components, silver-tin baking process muffle furnaces, superhard alloy manufacturing process fixtures, special powder (LED raw materials, etc.) baking process retorts (retorts) that need high temperature oxidation resistance and hot forging.

[0041] Example 1

[0042] The raw materials were mixed in a predetermined ratio and then melted in a vacuum melting furnace and cast to produce a 10 kg ingot of a Ni-based alloy having the alloy composition shown in Table 1. It should be noted that Alloy 10 corresponds to the Ni-based alloy of Patent Document 1. And Alloy 11 corresponds to the Ni-based alloy of Patent Document 2.

[0043] Next, the ingot was hot forged while being heated to 1200°C to produce a plate having a thickness of 25 mm and a width of 50 mm. It should be noted that the temperature of the plate at the end of hot forging was about 800°C. In addition, all Ni-based alloys can be forged into the above dimensions without cracks. The forged material was further machined to a length of 100 mm.

[0044] [Table 1]

[0045]

[0046] ※Contains impurities

[0047] The Ni-based alloys 1 to 5 and 10 and 11 were subjected to repeated oxidation tests as follows to evaluate the high temperature oxidation resistance.

[0048] First, 15×15×10mmt test pieces were made from the plate with a thickness of 25mm made as described above. Then, the surfaces of these test pieces were polished and finally finished with water-resistant sandpaper #300. The polished samples were immersed in each chemical in the order of metal cleaner, Fine Solve (made by Sankyo Chemical Co., Ltd.), and ethanol, and degreased using ultrasonic cleaning. In addition, the surface area (A0) was calculated by measuring the entire surface of the test piece, and the initial mass (W0) before the test was measured.

[0049] Next, a repeated oxidation test of repeatedly heating, holding and cooling was performed in the atmosphere on each test piece composed of Ni-based alloys 1 to 5 and 10 and 11. The test temperature was set to 700°C and the holding time was set to 1, 10, 100 and 1000 hours on a logarithmic scale. Figure 1 The thermal cycle of the test conditions is shown in Figure 1 In the figure, “RT” means room temperature).

[0050] exist Figure 1 At the end of each thermal cycle (number of repetitions X = 1 to 4), the mass (W) of the test piece is measured. x ). In addition, by x ) minus the initial mass (W0) and dividing this value by the surface area (A0) to calculate the mass change per unit surface area (ΔW x ). Mass change (ΔW x ) increases according to the rate of scale formation, and becomes negative when the scale peels off. x ) was plotted on a graph as the oxidation increment, and the generation and peeling morphology of oxide scale at each time was numerically understood to evaluate the high temperature oxidation resistance. The calculation was performed using the following formula (1). Figure 2 The results are shown.

[0051] ΔW x =(W x -W0) / A0 Formula (1)

[0052] from Figure 2 The results show that the high temperature oxidation resistance of the Ni-based alloys 1 to 5 of the present invention is superior to that of the comparative example Ni-based alloy 11. In particular, the high temperature oxidation resistance of the Ni-based alloy 4 is comparable to that of the Ni-based alloy 10, and the excellent high temperature oxidation resistance of the Ni-based alloy can be maintained even if the Cr content is reduced.

[0053] Example 2

[0054] The Ni-based alloys 1, 4, 5, 10, and 11 prepared in Example 1 were machined into plates with a thickness of 7 mm, a width of 17 mm, and a length of 60 mm, and heat-treated by air cooling from 900° C., assuming the form of the final product (i.e., for the purpose of grain size adjustment in the metallographic structure). Then, a square material with a thickness of 7 mm, a width of 17 mm, and a length of 17 mm was produced from the heat-treated plate by machining.

[0055] Next, the surface of the square material was polished and finally finished with water-resistant sandpaper #320. Three test pieces with a thickness of 5 mm, a width of 15 mm, and a length of 15 mm were made for each alloy. The polished test pieces were immersed in each chemical in the order of metal cleaner, FineSolve (produced by Sankyo Chemical Co., Ltd.), and ethanol, and degreased using ultrasonic cleaning. In addition, the surface area (A0) was calculated by measuring the entire surface of the test piece, and the initial mass (W0) before the test was measured. Next, the test piece was used to carry out an oxidation test in the same manner as in Example 1. It should be noted that the test temperature was set to 700°C, the number of thermal cycles was set to 1 (number of repetitions X = 1), and the holding time was set to 100h.

[0056] The mass change per unit surface area of ​​the test piece after the oxidation test (ΔW x ) is calculated as Figure 3 At this time, the mass change (ΔW x ) is the average value of the values ​​obtained from three test pieces of each alloy. The Ni-based alloy of the present invention example can maintain a very excellent high temperature oxidation resistance even if the Cr content is reduced.

[0057] Example 3

[0058] The raw materials were mixed in a predetermined ratio and then melted in a vacuum melting furnace and cast to produce a 10 kg ingot of a Ni-based alloy having the alloy composition shown in Table 2. It should be noted that alloy 12 is equivalent to the Ni-based alloy of Patent Document 1. In addition, alloy 13 is equivalent to the Ni-based alloy of Patent Document 2. In addition, alloys 14 to 16 are comparative Ni-based alloys containing only Mo without V.

[0059] Next, the ingot is hot forged while being heated to a temperature of 1200°C to produce a plate having a thickness of 25 mm and a width of 50 mm. It should be noted that at this time, the temperature of the plate at the end of hot forging is about 800°C. Moreover, all Ni-based alloys can be forged into the above-mentioned dimensions without cracking, etc. The forged material is further processed by machining into a plate having a thickness of 7 mm, a width of 17 mm, and a length of 60 mm. Then, assuming the form of the final product (i.e., for the purpose of graining the grains in the metallographic structure), the plate is subjected to a heat treatment of air cooling from 900°C, and then, a square material having a thickness of 7 mm, a width of 17 mm, and a length of 17 mm is produced by machining the heat-treated plate.

[0060] [Table 2]

[0061]

[0062] ※Contains impurities

[0063] The surfaces of the square materials of the above-mentioned Ni-based alloys 12 to 16 (comparative examples) and 17 to 26 (examples of the present invention) were polished and finally finished with water-resistant sandpaper #320. Three test pieces with a thickness of 5 mm, a width of 15 mm, and a length of 15 mm were made for each alloy. The polished test pieces were degreased, the surface area (A0) was calculated, and the initial mass (W0) before the test was measured in the same manner as in Example 1. Next, an oxidation test was carried out to evaluate the high-temperature oxidation resistance. It should be noted that the test temperature was set to 700°C, and the holding time was set to 1, 10, and 100 h. Then, the mass change (ΔW x It should be noted that the calculated mass change (ΔW x ) is taken as the average value of the values ​​of 3 test pieces for each alloy.

[0064] Figure 4 The retention time and mass change (ΔW x ) It should be noted that, here, the elements not added are recorded as "0"%. In addition, the results other than those of alloys 14, 21 to 26 are shown. First, by comparing alloys 13, 15, and 16, it is found that even a Ni-based alloy without V addition can change the mass of the conventional alloy 13 by adding Mo (ΔW x However, the amount of reduction is not as great as that of the alloys 17 to 20 of the present invention to which V in the amount of the present invention is added.

[0065] Furthermore, among the alloys 17 to 20 of the present invention, the mass changes (ΔW x ) are compared with the mass changes of alloys 17 and 18 (ΔW x ) is small. In addition, the mass change (ΔW x ) becomes smaller due to the large addition of Cr, and the mass change of alloy 20 (ΔW x ) becomes smaller than the mass change of alloy 12 (ΔW x It was confirmed that the addition of V according to the present invention and the simultaneous addition of Mo thereto are effective in improving oxidation resistance.

[0066] Regarding the above results, the V content of the Ni-based alloy containing Mo and the mass change (ΔW x ) are sorted according to their Mo content and the results are shown in Figure 5 .exist Figure 5In the graph, the circle marks are alloys containing about 0.25% Mo (alloys 14, 24, 25, 26), the square marks are alloys containing about 0.5% Mo (alloys 15, 19, 20, 21, 22), and the triangle marks are alloys containing about 1.0% Mo (alloy 23). These results show that, first, the mass change (ΔW) is increased by increasing the V content in the Ni-based alloy to about 0.5%. x ) is greatly reduced. It is also known that by increasing the V content to around 1.0%, the mass change (ΔW x ) is further reduced. Furthermore, from the comparison between alloys 14 and 15 without V addition and other alloys, it can be seen that the addition of Mo according to the present invention can only obtain the additional effect of improving oxidation resistance when it is performed in Ni-based alloys containing V.

[0067] Furthermore, the Ni-based alloy of the present invention can be forged without generating cracks in the above-mentioned hot forging process. Figure 5 The Ni-based alloys other than alloys 14 and 15 shown above were subjected to tensile tests assuming a forging end temperature of 800°C. Figure 6 and Figure 7 Basically, as the amount of V increases, the tensile strength of the Ni-based alloy increases and the elongation at break decreases, but the tensile strength of each is 360 MPa or less and the elongation at break is 20% or more, and it is judged that sufficient hot workability is maintained.

Claims

1. A Ni-based alloy having excellent high temperature oxidation resistance, characterized in that: It is composed of the following components: in mass %, it contains Al: 2.0-5.0%, Si: 0.1-2.5%, Mn: 0.1-1.5%, V: 0.4-3.0%, B: 0.001-0.05%, Zr: 0.001-0.1%, and the balance is Ni and impurities.

2. The Ni-based alloy having excellent high temperature oxidation resistance according to claim 1, characterized in that: The content of V is 1.0 to 3.0% by mass.

3. The Ni-based alloy having excellent high temperature oxidation resistance according to claim 1 or 2, characterized in that: Mo is further contained in mass %: 2.0% or less.

Citation Information

Patent Citations

  • Ni-BASED ALLOY EXCELLENT IN HOT FORGING PROPERTY, HIGH TEMPERATURE OXIDATION RESISTANCE AND HIGH TEMPERATURE HALOGEN GAS CORROSION PROPERTY AND MEMBER USING Ni-BASED ALLOY

    JP2014080675A

  • Ni-BASED ALLOY EXCELLENT IN HOT FORGEABILITY, HIGH-TEMPERATURE OXIDATION RESISTANCE AND RESISTANCE TO HIGH-TEMPERATURE HALOGEN GAS CORROSION AND MEMBER USING THE SAME

    JP2015045035A